Research into adventitious lung sound signals originating from pulmonary tuberculosis using electronic auscultation - Becker, Konrad Wilhelm (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.